The will of the empress - Pierce, Tamora (New York Scholastic Press, 2005)
On visit to Namorn to visit her vast landholdings and her devious cousin, Empress Berenene, eighteen-year-old Sandry must rely on her childhood friends and fellow mages, Daja, Tris, and Briar, despite the distance that has grown between them.
Keywords: Magic -- Fiction; Courts and courtiers -- Fiction; Kings, queens, rulers, etc. -- Fiction; Friendship -- Fiction; Fantasy